2021
DOI: 10.1128/jvi.00936-21
|View full text |Cite
|
Sign up to set email alerts
|

The Borna Disease Virus 2 (BoDV-2) Nucleoprotein Is a Conspecific Protein That Enhances BoDV-1 RNA-Dependent RNA Polymerase Activity

Abstract: An RNA virus-based episomal vector (REVec) based on Borna disease virus 1 (BoDV-1) is a promising viral vector that achieves stable and long-term gene expression in transduced cells. However, the onerous procedure of reverse genetics used to generate a REVec is one of the challenges that must be overcome to make REVec technologies practical for use. In this study, to resolve the problems posed by reverse genetics, we focused on BoDV-2, a conspecific virus of BoDV-1 in the Mammalian 1 orthobornaviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Furthermore, we showed that simultaneous transfection of M and G expression plasmids with N, P and L helper plasmids by reverse genetics significantly increases the rescue efficiency of rBoDV-1. Together with our recent report that upregulation of viral polymerase activity does not necessarily increase infectious particle production [9], these observations suggest that the expression levels of M and G, which are constituents of the viral lipid envelope, determine the number of progeny virions in infected cells.…”
supporting
confidence: 69%
See 4 more Smart Citations
“…Furthermore, we showed that simultaneous transfection of M and G expression plasmids with N, P and L helper plasmids by reverse genetics significantly increases the rescue efficiency of rBoDV-1. Together with our recent report that upregulation of viral polymerase activity does not necessarily increase infectious particle production [9], these observations suggest that the expression levels of M and G, which are constituents of the viral lipid envelope, determine the number of progeny virions in infected cells.…”
supporting
confidence: 69%
“…This feature also affects the rescue efficiency of recombinant BoDV-1 (rBoDV-1) by reverse genetics. To recover rBoDV-1 by reverse genetics, a vector plasmid transcribing the full-length antigenomic RNA of BoDV-1 and three helper plasmids expressing N, P and L were cotransfected into 293 T cells; however, this method allowed us to rescue only a small amount of infectious rBoDV-1 from transfected cells [9].…”
Section: Full-textmentioning
confidence: 99%
See 3 more Smart Citations